Een Hollands paleis in Limburg (Bulletin KNOB, 2006)
On 1 January 1924 the Rotterdam engineer Gustavus Cornelis (Kees) Bremer (1880-1949) was appointed as head of the unified Government Buildings Agency, with the title of chief government architect. Within Dutch modern architecture Bremer acted as a link between the architecture of H.R Berlage and of J.J.P. Oud by means of a powerful and monumental form language. The new 'Gouvernementsgebouw' (government building) in Maastricht is one of his major designs. The total work took approximately five years, from January 1930 to 1 July 1935, the date of the official opening.Bremer was confronted with a multifunctional assignment: not only an office and conference building, but also an official residence and pied-à-terre for the royal family. It is plausible that Bremer, who was looking for a typology for the complex, was inspired by the classical imperial buildings. In order not to affect the existing historical context, the brick- and natural- stone façades fit in with the old, simple roof-to-roof houses. The exterior with its severe austerity conceals the extravagant wealth of the interior.Limburg artists worked together on the iconographic programme, which had a strong political undertone: the fact that Limburg belonged to the Kingdom of the Netherlands, the protective and directive task of the state, the promise of freedom for the Roman-Catholic population in a Protestant country. From the iconographic point of view the tower is a symbol of the unity of the province belonging to the national state.